Tennessee Williams A Literary Life - Bak, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This Literary Life draws extensively from the playwright's correspondences, notebooks, and archival papers to offer an original angle to the discussion of Williams's life and work, and the times and circumstances that helped produce it.
Keywords: America—Literatures.; Literature, Modern—20th century; Fiction; Theater—History.; North American Literature; Twentieth-Century Literature; Fiction; Theatre History